Yield Ratios of the Isomeric Pair \(^{179m,g}\)W Produced in the \(^{nat}\)W(g,xn)\(^{179m,g}\)W Reactions with 50-65 MeV Bremsstrahlung - Do, Nguyen Van; Khue, Pham Duc; Xuan, Nguyen Thi; Loat, Bui Van; Hien, Nguyen Thi; Kim, Guinyun (Communications in Physics, 2017)
In this work we present the yield ratios of the \(^{179m,g}\)W isomeric pair produced in the photonuclear reactions \(^{nat}\)W(g,xn)\(^{179m,g}\)W  with bremsstrahlung end-point energies of 50-, 55-, 60-, and 65-MeV. The measurements were carried out by the induced activity method in combination with direct gamma-ray spectrometry. The measured activities were corrected for overlapping gamma-ray peaks, self-absorption of low energy gamma-rays and true coincidence summing effects. The present results  are measured for the first time with bremsstrahlung end-point energies beyond the giant dipole resonance region. The obtained results are discussed with respect to the incident bremsstrahlung energies and reaction channel effect.